Interval-valued Intuitionistic Fuzzy Weighted Entropy in Evaluation of Service Quality - Lazim Abdullah; Hui Mei Ling (Institute of Advanced Engineering and Science, 2013)
The importance of measuring service quality perceived by customers is an issue since the service quality is a key to success in service oriented industry. The estimation of service quality should be carried out with suitable measurement scales according to the types of service provided. To the best of authors’ knowledge, there have been little discussion about the applications of interval-valued intuitionistic fuzzy sets- based evaluation in measuring service quality. This paper proposes an evaluation for service quality of five vehicle insurance companies using interval-valued intuitionistic fuzzy entropy measure. Linguistic data were collected from customers using a questionnaire. An averaged interval-valued intuitionistic fuzzy number is used to construct decision matrix. Interval-valued intuitionistic fuzzy weighted averaging operator is used to aggregate the interval-valued intuitionistic fuzzy numbers for alternatives. It is found that PCF Insurance was evaluated as the best vehicle insurance company in providing service quality to customersDOI: http://dx.doi.org/10.11591/ij-ict.v2i1.1525